2020
DOI: 10.21203/rs.3.rs-121604/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parental Bonding Styles in Schizophrenia, Depressive and Bipolar Patients: A Comparative Study

Abstract: Background: Numerous bio-psychosocial factors play a role in the etiology of psychiatric disorders. In this regard, the relationship between parents and their children is significantly involved in developing the offspring mental health. However, there is no clear-cut answer as to which parental bonding style is more strongly associated with psychiatric diseases of patients. This study aimed to compare parental bonding styles in patients with schizophrenia, depression, and bipolar disorder in Bushehr province, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(37 reference statements)
0
1
0
1
Order By: Relevance
“…Specifically, both DysMB and DysPB were found to be related to psychological symptoms with largely similar effects. Although most existing studies highlight the importance of maternal bonding or mother–child attachment (Abbaspour et al, 2021; Eun et al, 2018), perceived dysfunctional parenting styles from fathers are also significant risk factors for mental illnesses (Eun et al, 2018; Hamza & Willoughby, 2011). For example, research with large population samples has demonstrated that parenting received from mothers and fathers during childhood was equally associated with adult mental health outcomes (Kendler et al, 2000; Otowa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, both DysMB and DysPB were found to be related to psychological symptoms with largely similar effects. Although most existing studies highlight the importance of maternal bonding or mother–child attachment (Abbaspour et al, 2021; Eun et al, 2018), perceived dysfunctional parenting styles from fathers are also significant risk factors for mental illnesses (Eun et al, 2018; Hamza & Willoughby, 2011). For example, research with large population samples has demonstrated that parenting received from mothers and fathers during childhood was equally associated with adult mental health outcomes (Kendler et al, 2000; Otowa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nicht nur eine wie auch immer motivierte (und hier können die Motive vielfältig sein) Ablehnung mit Emotionen von Hass und Entfremdung begründet durch eine schwere Störung der mütterlichen Bindung 1 , 16 , sondern auch eine zu starke Bindung kann zu Tötung des eigenen Kindes führen. Eine solche „tödliche Mutterliebe“ findet sich im v. a. im Kontext des erweiterten Suizids und insbesondere bei depressiv erkrankten Frauen.…”
Section: Gegenwärtige Mutterrolleunclassified